Evolução do tamanho de grão e comportamento mecânico do magnésio comercialmente puro submetido a tratamento termo-mecânico de ECAP - Claudio Laudares Passos Silva (2015)
In this work samples of commercially pure magnesium were processed by ECAP (Equal Channel Angular Pressing), in moderate temperatures, using a die with angle of = 135° between the two channels. An intermediate step of rolling was used to facilitate the processing and to avoid cracking, the samples was covered with a cooper sheet of 0.3 mm thickness to reduce friction between the sample and the die channel. The samples were processed by 4 steps of ECAP using route C, with punch speed of 10 mm/min. The microstructure of the material was evaluated using metallographic procedures. The material processed by rolling from 5 mm to a thickness of 1 mm + ECAP (4 steps) exhibits a completely refined and homogeneous microstructure with average grain size of 5 m. Tensile tests were used to determine mechanical behavior after and before ECAP and show an increase in ductility of the material processed by ECAP. The strain rate sensitivity coefficient was determined by true stress versus true strain curves obtained in the tensile tests of the material processed by rolling and the material processed by rolling and ECAP. The m values determined for the rolled material and for the material processed by ECAP were very similar.